The Relationship between Inflation and Political Stability - Ratu Melda Hermanda; Delia Febriana Ayuningtyas; Kenya Manggala Puteh; Moh. Aris Munandar; Hafiz Rafi Uddin (MultiTech Publisher, 2024)
This article examines the relationship between inflation and political stability in Indonesia. By using secondary data related to the level of inflation and the political situation from a certain period, this article aims to analyze whether there is a correlation between inflation and political stability in Indonesia, as well as the dynamics of this relationship. Through a statistical analysis approach and literature review, this research finds that the relationship between inflation and political stability in Indonesia tends to be complex and influences each other. Although high inflation rates can create social dissatisfaction and political pressure, there are also situations where political factors such as government stability and economic policy can influence inflation rates. The results of this analysis provide valuable insight for policymakers to design effective strategies for maintaining economic and political stability in Indonesia.